Liquidity Risks in the Context of Sustainable Development of a Commercial Company - S. A. Sidorova (Учёт. Анализ. Аудит)
The influence of liquidity risks on the sustainable development of a company is analyzed in the article. Herewith, the stages of financial strategy integration and sustainable development strategy are singled out. The first stage presupposes the maintenance of current financial sustainability. The second stage concerns long term financial sustainability. At the third stage we propose to consider the category of financial sustainability in the context of sustainable development in the process of value creation of the business. In doing so, we suggest considering the maintenance of financial sustainability as a complex notion in accordance with the demands of the main stakeholders including the satisfaction of the business owners. On each stage of the financial strategy integration we single out certain liquidity risks. In doing so, we describe the interconnection between the liquidity risks and the sustainable development of an economic entity with help of the category of financial sustainability. We suggest an analytical instrument which enables us to analyse the influence of liquidity risks on the sustainable development of an economic entity on each stage of financial strategy and sustainable development strategy integration. The methods suggested in the article are based on quality and quantity estimates. When working out the analytical instrument we took into consideration the fact that the appearance of liquidity risks is explained by investments in sustainable development of a commercial organization as well as by neglect of investments in different types of sustainability. The quality method was worked out on the basis of the criteria of sustainable development in accordance with the GOST (All-Union State Standard) ISO 26000–2012 and GRI. The analysis methods we suggest to measure the influence of liquidity risks on the sustainable development of a commercial organization are complementary to the existent methods of estimating and managing risks, known as the ERM methodology. Moreover, the methods we suggest in the article follow the concept of the ERM methodology, which is based on the assumption that risks do not only constitute a threat to the continuity of economic activity but also to the opportunity of further development with effective risk management. The analytical instrument in question is presented in an aggregative form therefore can be used by outside users of financial reports.